Correlation between Liver function tests, lipid profile and fibroscan in non-alcoholic fatty liver disease - Ali A. Ghweil; Hassan S. Mahmoud; Mohamed Elsenbesy; Amal Shahat Mohammed (SVU - International Journal of Medical Sciences, 2023)
Background: NAFLD is considered hepatic manifestation of metabolic syndrome, associated with multiple metabolic disturbances as diabetes and hyperlipidemia using Fibroscan as screening tool for steatosis and fibrosis in NAFLD patients. Objectives: The aim of this study is to elucidate the Correlation between Liver function test, Lipid Profile, Fibroscanin NAFLD. Patients and methods: this Prospective Cohort study conducted on 50 subjects with NAFLD and 15 Healthy subjects. Blood samples were obtained for liver function tests (ALT,AST, serum total bilirubin, serum direct bilirubin), lipogram, serology, fasting Blood glucose and HBA1c also abdominal ultrasonography and Fibrscan were done. Results: This study included 65persons that subdivided in to two groups 50 NAFLD patients and 15 healthy volunteer. With mean age of studied patients was 42 years and 32.3% were males and 67.7% were female. We found statistically significant higher values in NAFLD subjects as regard Diabetes mellitus, HBA1c and hypertension than in healthy subjects (p value .003, 0.001,0 .003) respectively. NAFLD subjects showed statistically moderately significant higher values as regard lab investigations (Triglycerides (TriGs), High density lipoprotein(HDL),ALT,AST, Direct bilirubin(Bili-D), Fasting blood glucose(FBG)), p value (.001) and show statistically significant lower value as regard cholesterol (p value = .004) compared to non NAFLD group. Regression analysis was done and revealed that fibroscan could predict the presence of NAFLD. Conclusion: there is strong relationship between liver function tests, lipid profile and fibroscan and diagnosis of NAFLD.